Relationship Between the Maturation of the Midpalatal Suture and the Mineralization of the Mandibular Second and Third Molars - Garcia Gonzales, Luis Angel (2025)
To assess the relationship between the maturation of the midpalatal suture (MPS) and the mineralization stages of the mandibular second molar (M2) and third molar (M3) using cone-beam computed tomography (CBCT). A descriptive, cross-sectional, retrospective, and correlational study was conducted. Of 456 available CBCT scans, 121 that met the selection criteria were evaluated. Patients’ ages ranged from 5 to 30 years and were distributed into five previously established age groups. A non-stratified sampling method was used to include all eligible cases and avoid data loss. Tomographic images were analyzed to determine the maturation stage of the MPS according to Angelieri’s method, and the mineralization stages of M2 and M3 were assessed using Demirjian’s classification. The correlation between MPS maturation and M2 mineralization showed a coefficient of 0.574, while the correlation between MPS maturation and M3 mineralization was 0.548; both indicated a moderate positive correlation. Statistical analysis was performed using Spearman’s correlation coefficient (p≤0.05). A significant relationship was found between midpalatal suture maturation and the mineralization of the mandibular second and third molars, enabling a more precise assessment of craniofacial development. Both sutural maturation and molar mineralization showed progressive advancement with chronological age, supporting their usefulness as biological growth indicators.